2014
DOI: 10.17219/acem/37215
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia Trachomatis Promotes 3T3 Cell Differentiation into Adipocytes

Abstract: Background. There is experimental and clinical evidence showing that some viral and bacterial pathogens are linked to the accumulation of excessive body fat and obesity. Objectives. The aim of the study was to investigate the ability of C. trachomatis to propagate in the pre-adipocyte cell line and induce its differentiation into fat cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The vital role of lipids as intracellular nutrients for the proliferation of Chlamydia has been documented [ 125 , 126 ]. A current in vitro study has shown the ability of Chlamydia to infect preadipocytes and promote their differentiation to adipocytes in the 3T3-L1 cell line, suggesting the possibility that Chlamydia can induce infectobesity [ 127 ]. The animal models support the idea that Chlamydia activates lipid pathways during infection.…”
Section: Adipocytes As Infection Targets and Their Relationship With ...mentioning
confidence: 99%
“…The vital role of lipids as intracellular nutrients for the proliferation of Chlamydia has been documented [ 125 , 126 ]. A current in vitro study has shown the ability of Chlamydia to infect preadipocytes and promote their differentiation to adipocytes in the 3T3-L1 cell line, suggesting the possibility that Chlamydia can induce infectobesity [ 127 ]. The animal models support the idea that Chlamydia activates lipid pathways during infection.…”
Section: Adipocytes As Infection Targets and Their Relationship With ...mentioning
confidence: 99%
“…138 The proposed mechanisms involve worsening insulin resistance in the setting of prediabetes or diabetes, and propagating differentiation of the preadipocyte cell line into mature fat cells. 139 The obesity-associated patterns in gut microbiota inherently impaired neurocognitive behavior in an experimental setting by disturbing intestinal barrier function, increasing circulating endotoxins, and increasing lymphocyte expression of some of the calcium-binding receptors. 140 These patterns increased neuroinflammation and disrupted cerebrovascular homeostasis.…”
Section: Environmental Mechanismsmentioning
confidence: 99%
“…Such intracellular bacteria may also be associated with development of neurodegenerative and behavioral disorders. For example, there is evidence that Chlamydophila pneumoniae may promote differentiation of preadipocyte cells into mature fat cells and be possibly associated with development of metabolic syndrome, fatty liver, or nonalcoholic steatohepatitis [ 3 ].…”
Section: Introductionmentioning
confidence: 99%